2020
DOI: 10.3389/fimmu.2020.01920
|View full text |Cite
|
Sign up to set email alerts
|

Update on Transplacental Transfer of IgG Subclasses: Impact of Maternal and Fetal Factors

Abstract: information regarding levels and transfer of IgG subclasses in healthy term pregnancies and demonstrates the importance of recording detailed clinical information in studies of antibody transfer, including parity, ethnicity, and timing of maternal vaccine delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
2
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 37 publications
6
84
2
1
Order By: Relevance
“…IgG1, IgG3, or IgG4 transferred better than IgG2, except for S. pneumoniae , for which IgG2 transfer was significantly higher. This was unexpected as classically it has been described that the greatest transport occurs for IgG1, followed by IgG4, IgG3, and finally IgG2 ( 20 ), although a recent report showed a different hierarchy of subclass transfer and identified a number of other studies that also observed different transfer efficiencies, depending on the antigen tested ( 21 ). However, IgG1 levels were the highest for almost all antigens in cord blood, probably because of the overall higher levels of this IgG subclass in maternal blood.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…IgG1, IgG3, or IgG4 transferred better than IgG2, except for S. pneumoniae , for which IgG2 transfer was significantly higher. This was unexpected as classically it has been described that the greatest transport occurs for IgG1, followed by IgG4, IgG3, and finally IgG2 ( 20 ), although a recent report showed a different hierarchy of subclass transfer and identified a number of other studies that also observed different transfer efficiencies, depending on the antigen tested ( 21 ). However, IgG1 levels were the highest for almost all antigens in cord blood, probably because of the overall higher levels of this IgG subclass in maternal blood.…”
Section: Discussionmentioning
confidence: 86%
“…Only IgG is transferred across the placenta with the highest rate occurring during the third trimester of pregnancy ( 17 ), although some studies suggest that maternal IgE may also be transferred to the fetus as IgG/IgE complexes ( 18 ). IgG subclasses have different affinities for the FcRn receptor leading to differences in the efficiency of transfer ( 19 ); classically it was stated that the greatest transport occurs for IgG1, followed by IgG4, IgG3, and finally IgG2 ( 20 ), although a recent update on transplacental transfer of IgG subclasses showed that it is different depending on the antigen and study populations ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the role of antibodies in binding and neutralization, antibodies contribute to protection against COVID-19 disease through their ability to recruit the innate immune response with their Fc-domain (18,19). The Fc-functions of the humoral immune response play a critical role in resolution of , are associated with protection from infection following vaccination (21), play a critical role in antibody transfer across the placenta (22)(23)(24)(25) and may also influence transfer into breastmilk (26). To define qualitative features of the vaccine-induced humoral immune response across pregnancy and early life, here we comprehensively profiled the humoral immune response following mRNA vaccination in pregnant, lactating, or non-pregnant women who received the Pfizer/BioNTech or the Moderna vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, though IgG1-4 can all be detected in fetal circulation, there is an especially high quantity of IgG1. Data support a general transfer hierarchy of IgG subclasses, which is believed to be IgG1 > IgG4 > IgG3 > IgG2, although deviation from this hierarchy in regard to IgG2, IgG3, and IgG4 transport has been reported across study populations [ 23 , 60 , 61 , 62 ]. As one might expect, binding between FcRn and IgG is critical to this transfer: a recombinant H435A-bearing IgG1 with undetectable affinity for human FcRn exhibited a ~90% reduction in transfer rate ex vivo [ 63 ].…”
Section: Fcrn Expression and Its Effects On Homeostatic Igg Distrimentioning
confidence: 78%